Estudo de agregados e ligantes alternativos para emprego em tratamentos superficiais de rodovias - Loiola, Paulo Roberto Reis (2009)
The superficial treatment can be defined as a coating of low cost, consisting of a slender layer of asphalt binder and mineral aggregate. It has been used in most of the roads in Ceará with low to medium traffic volume, existing few studies for this covering type in the technical middle and academic. The main objective of this study was to evaluate the performance of mineral aggregate and steel slag applied with conventional emulsions and modified by polymer coating for double surface treatment. For this purpose, were cast in the laboratory and field tests on asphalt blankets, coverings, double surface treatment, with applications of mineral aggregate and steel slag with asphalt emulsion RR-2C (modified whith polymer and not modified polymer). For analysis of the taxes of the different aggregate and binder the asphalt blankets were submitted to the tested in the Wet Track Abrasion Test (WTAT). The coatings fabricate were also subjected to tests Spot Sand and Pendulum British to analyze the characteristics of their textures. The aggregates were subjected to tests of resistance to abrasion Los Angeles, shape and texture, density, absorption, particle size, adhesiveness, durability, chemical analysis, scalability, solubilization and leaching. Samples of emulsion were evaluated using laboratory tests such as viscosity, Saybolt Furol, sedimentation, particle charge, residue by evaporation, sifting, pH, breaking rate emulsifying, penetration, elastic recovery, softening point and ductility. Aggregates and emulsions used had characteristics suitable for application in surface treatment. The results for WTAT, Channel Sand and British Pendulum tests showed the technical feasibility of materials for use in surface treatment.